Mobile phone involvement, beliefs, and texting while driving in Ukraine. (April 2019) - Hill, T.; Sullman, M.J.M.; Stephens, A.N.
Highlights: The study was conducted in Ukraine. The study adopted a beliefs-based theory of planned behaviour approach. Psychological factors associated with mobile phone use while driving were explored. Gender, MPIQ scores and beliefs were associated with mobile phone use while driving. Abstract: There is extensive evidence that using a mobile phone whilst driving is one of the biggest contributors to driver distraction, which in turn increases the risk of motor vehicle collisions. Whilst most of the developed countries have been trying to deter this behaviour through legislation, enforcement and educational campaigns, in Ukraine, where the road fatality rate is the highest in Europe, this issue has only recently become publicised. The present study examined psychological factors that are associated with hand-held mobile phone use while driving among a sample of Ukrainian drivers, in particular writing or reading a text message while driving. This included drivers' behavioural, normative, and control beliefs relating to mobile phone use while driving, as well as the degree to which using a mobile phone is integral to one's everyday life (measured using the Mobile Phone Involvement Questionnaire; MPIQ). Almost one quarter to one third of the sample reported using their phone on a daily basis to write (22.2%) or read (38.2%) text messages while driving. A binary logistic regression showed that gender, higher MPIQ scores, perceived approval from family members, lower perceived likelihood of receiving traffic fines and less demanding traffic conditions were all significantly associated with mobile phone use while driving. These results suggest that dependence upon a mobile phone in everyday life may be an important factor to consider when developing interventions to reduce hand-held mobile phone use while driving.